Wear-resistant anticorrosion composite coating, engine piston and engine

CN224901451UActive Publication Date: 2026-10-27BEIFANG UNIV OF NATITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202522501963.6
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-11-25
Publication Date
2026-10-27
Estimated Expiration
2035-11-25

AI Technical Summary

Technical Problem

[0004]目前,由PVD技术制备的活塞保护涂层有TiN、CrCN、TiAlN等,这些金属碳氮化物涂层具有硬度高、耐腐蚀等特点,但摩擦系数较高

Benefits of technology

[0024]本申请实施例的有益效果包括,例如:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224901451U_ABST
    Figure CN224901451U_ABST
Patent Text Reader

Abstract

The embodiment of the application provides a wear-resistant anticorrosion composite coating, an engine piston and an engine, and relates to the field of coating technology. The wear-resistant anticorrosion composite coating is arranged on the surface of an AlSi alloy and comprises a coating group arranged on the surface of the AlSi alloy, wherein the coating group comprises a Cr coating, a CrN coating, a CrCN coating and a DLC coating which are sequentially arranged on the surface of the AlSi alloy. The arrangement of the composite coating can improve the bonding strength between the coating and the AlSi alloy, prevent the coating from falling off, improve the corrosion resistance of the coating, reduce the friction coefficient and improve the wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of coating technology, and more specifically, to a wear-resistant and corrosion-resistant composite coating, an engine piston, and an engine. Background Technology During engine piston operation, the various components move relative to each other, making the fretting wear between the piston pin bore and the piston pin shaft significant. Simultaneously, the stress and friction generated during contact between these components make the piston pin bore highly susceptible to wear and failure. Extensive analysis shows that the piston pin bore and piston pin are high-risk areas for failure in piston assemblies, and in severe cases, can lead to overall piston failure. Therefore, the wear resistance of the piston pin plays a decisive role in the service life and reliability of engine pistons.

[0002] With the rapid development of surface treatment technology, aluminum alloy piston surface treatment has evolved to include techniques such as plasma spraying, micro-arc oxidation, and anodizing. These techniques offer advantages such as high coating bonding strength, high coating thickness, and good high-temperature resistance, but they also suffer from problems like high coating porosity and high surface roughness. In recent years, with the application of vapor deposition technology, the porosity within the coating has decreased, the density has increased, and the surface quality of the coating has been improved.

[0003] Currently, there are two main methods of vapor deposition: chemical vapor deposition (CVD) and physical vapor deposition (PVD). Compared with other surface treatments, PVD has advantages such as high preparation efficiency, strong controllability, high coating hardness, and high purity, and is widely used in aerospace, automotive and other industries.

[0004] Currently, piston protective coatings prepared by PVD technology include TiN, CrCN, and TiAlN. These metal carbonitride coatings have the characteristics of high hardness and corrosion resistance, but also a high coefficient of friction. Utility Model Content

[0005] The purpose of this application includes, for example, providing a wear-resistant and corrosion-resistant composite coating, an engine piston, and an engine, which can improve the wear resistance and corrosion resistance of the coating and improve the corrosion protection efficiency of the coating.

[0006] The embodiments of this application can be implemented as follows: In a first aspect, this application provides a wear-resistant and corrosion-resistant composite coating for application on the surface of an AlSi alloy, comprising: a coating group applied to the surface of the AlSi alloy, the coating group comprising a Cr coating, a CrN coating, a CrCN coating and a DLC coating sequentially stacked on the surface of the AlSi alloy.

[0007] In the above technical solution, the AlSi alloy matrix is ​​relatively soft, and the increased hardness gradient of the Cr, CrN, CrCN, and DLC coatings ensures high bonding strength between the coatings and the AlSi alloy matrix. This prevents the coatings from detaching due to insufficient bonding strength caused by the large hardness gradient. Furthermore, the DLC coating, composed of amorphous carbon material with sp²-C and sp³-C hybrid bonds, exhibits a synergistic effect that combines the lubricity of graphite with the mechanical properties of diamond, displaying high hardness, high elastic modulus, low coefficient of friction, low wear rate, low surface roughness, high insulation, and excellent corrosion resistance. Therefore, the DLC coating has significant advantages in friction reduction, wear resistance, and self-lubrication. In summary, the above composite coating configuration achieves high bonding strength between the coating and the AlSi alloy, preventing coating detachment, while also providing good corrosion resistance, a low coefficient of friction, and good wear resistance.

[0008] In an optional embodiment, the coating group comprises 1 to 10 groups stacked together.

[0009] In the above technical solution, the setting of multiple coating groups can further improve the corrosion resistance and wear resistance of the coating.

[0010] In an optional embodiment, the coating group comprises 4-5 groups stacked together.

[0011] In the above technical solution, the coating group is set to 4-5 groups, which can significantly reduce the friction coefficient of the composite coating, and there is a clear passivation range. The breakdown voltage is high, the passivation film is not easily damaged, and the corrosion point of the coating is high, the corrosion current density is low, the corrosion rate is slow, and the corrosion protection efficiency is high.

[0012] In an optional embodiment, the thickness ratio of the Cr coating, the CrN coating, the CrCN coating and the DLC coating is (2-4):(2-12):(10-20):(10-60) respectively; the total thickness of the composite coating is 400nm-1200nm.

[0013] In the above technical solution, the thickness of each layer of the coating meets the ratio and the total thickness meets the range, which can further improve the wear resistance and corrosion resistance of the composite coating.

[0014] Secondly, this application provides a wear-resistant and corrosion-resistant composite coating for application on the surface of an AlSi alloy, comprising: a coating group applied to the surface of the AlSi alloy, wherein the coating group comprises a Cr coating, a CrN coating, a CrTiCN coating and a DLC coating sequentially stacked on the surface of the AlSi alloy.

[0015] In the above technical solution, the AlSi alloy substrate is relatively soft, and the increased hardness gradient of the Cr coating, CrN coating, CrTiCN coating, and DLC coating ensures high bonding strength between the coating and the AlSi alloy substrate. This prevents insufficient bonding strength and coating detachment due to the large hardness gradient. Furthermore, the DLC coating offers significant advantages in friction reduction, wear resistance, and self-lubrication. In addition, the addition of Ti to the CrTiCN coating further reduces the coefficient of friction, particularly in seawater, thus improving seawater corrosion resistance. In summary, the above composite coating setup achieves high bonding strength between the coating and the AlSi alloy, preventing coating detachment, while also providing good seawater corrosion resistance, a low coefficient of friction, and good wear resistance.

[0016] In an optional embodiment, the coating group comprises 1 to 10 groups stacked together.

[0017] In the above technical solution, the setting of multiple coating groups can further improve the corrosion resistance and wear resistance of the coating.

[0018] In an optional embodiment, the coating group comprises 4-5 groups stacked together.

[0019] In the above technical solution, the coating group is set to 4-5 groups, which can significantly reduce the friction coefficient of the composite coating. Furthermore, the coating exhibits a self-healing process of passivation film in seawater, with a wide passivation range, further improving its resistance to seawater corrosion.

[0020] In an optional embodiment, the thickness ratio of the Cr coating, the CrN coating, the CrTiCN coating and the DLC coating is (2-4):(2-12):(10-40):(10-60) respectively; the total thickness of the composite coating is 400-1200 nm.

[0021] In the above technical solution, the thickness of each layer of the coating meets the ratio and the total thickness meets the range, which can further improve the wear resistance and seawater corrosion resistance of the composite coating.

[0022] Thirdly, this application provides an engine piston, including an AlSi alloy piston substrate, and a wear-resistant and corrosion-resistant composite coating as described in any of the preceding embodiments disposed on the surface of the piston substrate.

[0023] Fourthly, this application provides an engine including the engine piston described in any of the foregoing embodiments.

[0024] The beneficial effects of the embodiments of this application include, for example: In this application, the AlSi alloy matrix is ​​relatively soft, and the hardness gradient of the Cr coating, CrN coating, CrCN coating, and DLC coating increases, resulting in high bonding strength between the coating and the AlSi alloy matrix. This prevents the coating from detaching due to insufficient bonding strength caused by a large hardness gradient. Furthermore, the DLC coating is an amorphous carbon material composed of sp²-C and sp³-C hybrid bonds. The synergistic effect of these two hybrid bonds gives it both the lubricity of graphite and the mechanical properties of diamond, exhibiting high hardness, high elastic modulus, low coefficient of friction, low wear rate, low surface roughness, high insulation, and excellent corrosion resistance. Therefore, the DLC coating has significant advantages in friction reduction, wear resistance, and self-lubrication. In summary, the above-mentioned composite coating configuration ensures high bonding strength between the coating and the AlSi alloy, preventing coating detachment, and also provides good corrosion resistance, a low coefficient of friction, and good wear resistance.

[0025] Furthermore, replacing the CrCN coating with a CrTiCN coating, and adding Ti to the CrTiCN coating, can further reduce the coefficient of friction of the coating, especially in seawater, and further improve its resistance to seawater corrosion. Attached Figure Description

[0026] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0027] Figure 1 A schematic diagram of the first layer structure of the wear-resistant and corrosion-resistant composite coating provided in this application; Figure 2 A schematic diagram of the second layer structure of the wear-resistant and corrosion-resistant composite coating provided in this application; Figure 3 The friction coefficient curves of the composite coatings provided in Examples 1-5 of this application are shown. Figure 4 The polarization curves of the composite coatings provided in Examples 1-5 of this application are shown. Figure 5 Friction coefficient curves of the composite coatings provided in Examples 6-10 of this application; Figure 6 Polarization curves of the composite coatings provided in Examples 6-10 of this application.

[0028] Icons: 110-AlSi alloy; 120-Cr coating; 130-CrN coating; 141-CrCN coating; 150-DLC coating; 142-CrTiCN coating. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. The components of the embodiments of this application described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.

[0030] Therefore, the following detailed description of the embodiments of this application provided in the accompanying drawings is not intended to limit the scope of the claimed application, but merely to illustrate selected embodiments of the application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.

[0031] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.

[0032] In the description of this application, it should be noted that if terms such as "upper," "lower," "inner," or "outer" are used to indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship in which the product of the invention is usually placed during use, they are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.

[0033] Furthermore, the terms "first" and "second" are used only to distinguish descriptions and should not be interpreted as indicating or implying relative importance.

[0034] It should be noted that, where there is no conflict, the features in the embodiments of this application can be combined with each other.

[0035] Please refer to Figure 1 This embodiment provides a wear-resistant and corrosion-resistant composite coating for application on the surface of AlSi alloy 110, comprising: a coating group applied to the surface of AlSi alloy 110, the coating group comprising a Cr coating 120, a CrN coating 130, a CrCN coating 141 and a DLC coating 150 sequentially stacked on the surface of AlSi alloy 110.

[0036] Among them, AlSi alloy 110, Cr coating 120, CrN coating 130, CrCN coating 141 and DLC coating 150 (diamond-like coating) are all existing material layer structures, and this application does not improve the composition of the layer structure.

[0037] In the above technical solution, the AlSi alloy 110 substrate is relatively soft, and the increased hardness gradient of the Cr coating 120, CrN coating 130, CrCN coating 141, and DLC coating 150 ensures high bonding strength between the coatings and the AlSi alloy 110 substrate. This prevents the coatings from detaching due to insufficient bonding strength caused by the large hardness gradient. Furthermore, the DLC coating 150 is an amorphous carbon material composed of sp²-C and sp³-C hybrid bonds. The synergistic effect of these two hybrid bonds gives it both the lubricity of graphite and the mechanical properties of diamond, exhibiting high hardness, high elastic modulus, low coefficient of friction, low wear rate, low surface roughness, high insulation, and excellent corrosion resistance. Therefore, the DLC coating 150 has significant advantages in friction reduction, wear resistance, and self-lubrication. In summary, the above composite coating configuration ensures high bonding strength between the coating and the AlSi alloy, preventing coating detachment, and also provides good corrosion resistance, a low coefficient of friction, and good wear resistance.

[0038] In an optional embodiment, the coating group comprises 1-10 groups stacked together (wherein, Figure 1 (The example is illustrated with two coating groups.) Setting up multiple coating groups can further improve the corrosion resistance and abrasion resistance of the coating.

[0039] As an example, the coating group can be 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 groups. Optionally, the coating group includes 4-5 groups stacked together. Setting the coating group to 4-5 groups can significantly reduce the friction coefficient of the composite coating, and there is a clear passivation range, higher breakdown voltage, and the passivation film is not easily damaged. This results in a high number of corrosion sites, low corrosion current density, slow corrosion rate, and high corrosion protection efficiency.

[0040] In an optional embodiment, the thickness ratio of the Cr coating 120, the CrN coating 130, the CrCN coating 141, and the DLC coating 150 is (2-4):(2-12):(10-20):(10-60), respectively; the total thickness of the composite coating is 400-1200 nm. When the thickness of each layer of the coating meets this ratio and the total thickness meets this range, the wear resistance and corrosion resistance of the composite coating can be further improved.

[0041] Please see Figure 2This embodiment provides a wear-resistant and corrosion-resistant composite coating for application on the surface of AlSi alloy 110, comprising: a coating group applied to the surface of AlSi alloy 110, the coating group comprising a Cr coating 120, a CrN coating 130, a CrTiCN coating 142 and a DLC coating 150 sequentially stacked on the surface of AlSi alloy 110.

[0042] Among them, AlSi alloy 110, Cr coating 120, CrN coating 130, CrTiCN coating 142 and DLC coating 150 are all existing material layer structures, and this application does not improve the composition of these layer structures.

[0043] In the above technical solution, the AlSi alloy 110 substrate is relatively soft, and the increased hardness gradient of the Cr coating 120, CrN coating 130, CrTiCN coating 142, and DLC coating 150 ensures high bonding strength between the coatings and the AlSi alloy 110 substrate. This prevents insufficient bonding strength and coating detachment due to the large hardness gradient. Furthermore, the DLC coating 150 exhibits significant advantages in friction reduction, wear resistance, and self-lubrication. In addition, the addition of Ti to the CrTiCN coating 142 further reduces the coefficient of friction, particularly in seawater, and improves seawater corrosion resistance. In summary, the above composite coating configuration achieves high bonding strength between the coating and AlSi alloy 110, preventing coating detachment, while also providing good seawater corrosion resistance, a low coefficient of friction, and good wear resistance.

[0044] In an optional embodiment, the coating group comprises 1-10 groups stacked together (wherein, Figure 2 (The example is illustrated with two coating groups.) Setting up multiple coating groups can further improve the corrosion resistance and abrasion resistance of the coating.

[0045] As an example, the coating group may be 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 groups. Optionally, the coating group may include 4-5 groups stacked together. Setting the coating group to 4-5 groups can significantly reduce the friction coefficient of the composite coating, and the coating exhibits a self-healing process of passivation film in seawater, with a wide passivation range, further improving its resistance to seawater corrosion.

[0046] In an optional embodiment, the thickness ratio of the Cr coating 120, the CrN coating 130, the CrTiCN coating 142, and the DLC coating 150 is (2-4):(2-12):(10-40):(10-60), respectively; the total thickness of the composite coating is 400-1200 nm. When the thickness of each layer of the coating meets this ratio and the total thickness meets this range, the wear resistance and seawater corrosion resistance of the composite coating can be further improved.

[0047] This embodiment provides an engine piston, including an AlSi alloy 110 piston base, and a wear-resistant and corrosion-resistant composite coating as described in any of the preceding embodiments disposed on the surface of the piston base.

[0048] This embodiment provides an engine, including the engine piston described in any of the foregoing embodiments.

[0049] This application does not improve the engine piston or the engine structure. The engine or its structure will not be described in detail here. This application only improves the coating on the engine piston.

[0050] Example 1 Methods for preparing composite coatings include: (1) Provide an AlSi alloy plate with a thickness of 3 mm, clean the alloy plate with anhydrous ethanol, and dry it to obtain the matrix; (2) High-purity metallic chromium with a purity of 99.9% or higher is used as the target material, and magnetron sputtering is performed in a high-purity argon atmosphere to form a Cr coating with a thickness of 40 nm on the substrate. (3) Using high-purity metallic chromium with a purity of 99.9% or higher as the target material, magnetron sputtering is performed in an environment of high-purity argon mixed with nitrogen (the volume ratio of argon to nitrogen is 2:1) to form a CrN coating with a thickness of 120 nm on the Cr coating. (4) Using high-purity metallic chromium target and graphite target with a purity of 99.9% or higher, magnetron sputtering is performed in an environment of high-purity argon mixed with nitrogen (the volume ratio of argon to nitrogen is 2:1) and a methane environment (the volume ratio of argon, nitrogen and methane is 5:1:1) to form a CrCN coating with a thickness of 200 nm on the CrN coating. (5) Introduce acetylene gas and use plasma enhanced chemical vapor deposition (PECVD) to form a DLC coating with a thickness of 600 nm on the CrCN coating.

[0051] The above-mentioned coating group includes one group, referred to as Example 1:1.

[0052] Example 2 The difference between Example 2 and Example 1 is as follows: Steps (2)-(5) are performed twice in sequence. The total thickness of the composite coating obtained is the same as that of Example 1. The thickness of each layer of coating is half the thickness of the coating in Example 1, which is recorded as Example 1:2.

[0053] Example 3 The difference between Example 3 and Example 1 is as follows: Steps (2)-(5) are performed four times in sequence. The total thickness of the composite coating obtained is consistent with that of Example 1. The thickness of each layer of coating is 0.25 times that of the coating thickness of Example 1, which is recorded as Example 1:4.

[0054] Example 4 The difference between Example 4 and Example 1 is as follows: Steps (2)-(5) are performed five times in sequence. The total thickness of the composite coating obtained is consistent with that of Example 1. The thickness of each layer of coating is 0.2 times that of the coating thickness of Example 1, which is recorded as Example 1:5.

[0055] Example 5 The difference between Example 5 and Example 1 is as follows: Steps (2)-(5) are performed ten times in sequence. The total thickness of the composite coating obtained is consistent with that of Example 1. The thickness of each layer of coating is 0.1 times the thickness of the coating in Example 1, which is recorded as Example 1:10.

[0056] Experimental Example 1 The coefficient of friction of the composite coatings provided in Examples 1-5 was tested respectively, and the results were obtained. Figure 3 ,in Figure 3 The graph on the left shows the dry friction coefficient curve of the composite coating in the atmosphere. Figure 3 The graph on the right shows the friction coefficient curve of the composite coating in artificial seawater. Polarization tests were conducted on the composite coatings provided in Examples 1-5 under different voltages to obtain... Figure 4 .from Figure 3 and Figure 4 As can be seen, the coefficient of friction of the composite coating is below 0.2 in both environments, and the dry friction coefficient of the coating in Example 3 (the 1:4 curve in the figure) is about 0.09, while the friction coefficient in artificial seawater is about 0.10. This demonstrates that the composite coating reduces the coefficient of friction. Figure 5 The polarization curves of different coatings show that the composite coating provided in this application further improves the corrosion resistance. In Example 3 (the 1:4 curve in the figure), the film also has a clear passivation range with a high breakdown voltage of -0. V. The passivation film is not easily damaged, and the passivation voltage (-0. V), passivation current, and passivation maintenance current (7. × 10-8 A / cm2) are also the smallest. This indicates that the film is easier to passivate. The film has a high corrosion potential, the lowest corrosion current density, and a slow corrosion rate. The film also has the largest capacitive arc radius, and the resistance value of corrosion ions passing through the film is large, resulting in better corrosion resistance.

[0057] Example 6 Methods for preparing composite coatings include: (1) Provide an AlSi alloy plate with a thickness of 3 mm, clean the alloy plate with anhydrous ethanol, and dry it to obtain the matrix; (2) High-purity metallic chromium with a purity of 99.9% or higher is used as the target material, and magnetron sputtering is performed in a high-purity argon atmosphere to form a Cr coating with a thickness of 40 nm on the substrate. (3) Using high-purity metallic chromium with a purity of 99.9% or higher as the target material, magnetron sputtering is performed in an environment of high-purity argon mixed with nitrogen (the volume ratio of argon to nitrogen is 2:1) to form a CrN coating with a thickness of 120 nm on the Cr coating. (4) High-purity metallic chromium and titanium with a purity of 99.9% or higher are used as target materials and graphite target materials. Magnetron sputtering is performed in an environment of high-purity argon mixed with nitrogen and methane (the volume ratio of argon, nitrogen and methane is 2:1) to form a CrTiCN coating with a thickness of 400 nm on the CrN coating. (5) Acetylene gas is introduced and plasma-enhanced chemical vapor deposition (PECVD) is used to form a DLC coating with a thickness of 600 nm on the CrTiCN coating.

[0058] The above-mentioned coating group includes one group, referred to as Example 1:1.

[0059] Example 7 The difference between Example 7 and Example 6 is as follows: Steps (2)-(5) are performed twice in sequence. The total thickness of the composite coating obtained is consistent with that of Example 1. The thickness of each layer of coating is half of the thickness of the coating in Example 1, which is recorded as Example 1:2.

[0060] Example 8 The difference between Example 8 and Example 6 is as follows: Steps (2)-(5) are performed four times in sequence. The total thickness of the composite coating obtained is consistent with that of Example 1. The thickness of each layer of coating is 0.25 times that of the coating thickness of Example 1, which is recorded as Example 1:4.

[0061] Example 9 The difference between Example 9 and Example 6 is as follows: Steps (2)-(5) are performed five times in sequence. The total thickness of the composite coating obtained is consistent with that of Example 1. The thickness of each layer of coating is 0.2 times that of the coating thickness of Example 1, which is recorded as Example 1:5.

[0062] Example 10 The difference between Example 10 and Example 6 is as follows: Steps (2)-(5) are performed ten times in sequence. The total thickness of the composite coating obtained is consistent with that of Example 1. The thickness of each layer of coating is 0.1 times the thickness of the coating in Example 1, which is recorded as Example 1:10.

[0063] Experimental Example 2 The coefficient of friction of the composite coatings provided in Examples 6-10 was tested respectively, and the results were obtained. Figure 5 ,in Figure 5 The graph on the left shows the dry friction coefficient curve of the composite coating in the atmosphere. Figure 5 The graph on the right shows the friction coefficient curve of the composite coating in artificial seawater. Polarization tests were conducted on the composite coatings provided in Examples 6-10 under different voltages to obtain... Figure 6 .from Figure 5 and Figure 6 As can be seen, even with the addition of metallic Ti to the CrNC layer, the coefficient of friction of the coating remains low, especially in seawater where the coefficient of friction decreases. Figure 5 As shown, the polarization curves indicate that there is a self-healing process of the passivation film in the seawater, the passivation range is widened, and the seawater corrosion resistance is further improved.

[0064] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A wear-resistant and corrosion-resistant composite coating, characterized in that, For application on the surface of an AlSi alloy, comprising: a coating group disposed on the surface of the AlSi alloy, the coating group comprising a Cr coating, a CrN coating, a CrCN coating and a DLC coating sequentially stacked on the surface of the AlSi alloy.

2. The wear-resistant and corrosion-resistant composite coating according to claim 1, characterized in that: The coating group comprises 1 to 10 groups stacked together.

3. The wear-resistant and corrosion-resistant composite coating according to claim 1, characterized in that: The coating group comprises 4-5 groups stacked together.

4. The wear-resistant and corrosion-resistant composite coating according to any one of claims 1-3, characterized in that: The thickness ratios of the Cr coating, the CrN coating, the CrCN coating, and the DLC coating are (2-4):(2-12):(10-20):(10-60); the total thickness of the composite coating is 400-1200 nm.

5. A wear-resistant and corrosion-resistant composite coating, characterized in that, For application on the surface of an AlSi alloy, comprising: a coating group disposed on the surface of the AlSi alloy, the coating group comprising a Cr coating, a CrN coating, a CrTiCN coating and a DLC coating sequentially stacked on the surface of the AlSi alloy.

6. The wear-resistant and corrosion-resistant composite coating according to claim 5, characterized in that: The coating group comprises 1 to 10 groups stacked together.

7. The wear-resistant and corrosion-resistant composite coating according to claim 6, characterized in that: The coating group comprises 4-5 groups stacked together.

8. The wear-resistant and corrosion-resistant composite coating according to any one of claims 5-7, characterized in that: The thickness ratios of the Cr coating, the CrN coating, the CrTiCN coating, and the DLC coating are (2-4):(2-12):(10-40):(10-60); the total thickness of the composite coating is 400-1200 nm.

9. An engine piston, characterized in that: A piston substrate comprising an AlSi alloy, wherein the wear-resistant and corrosion-resistant composite coating of any one of claims 1-8 is disposed on the surface of the piston substrate.

10. An engine, characterized in that: Includes the engine piston as described in claim 9.